Impact of accuracy in anticipation on decomposition of autonomic tonic and phasic responses as predictor of performance excellence in Malaysian swimmers - Saha, Srilekha (2012)
Present study was aimed at identification of intricate relationship between the ability of the high performing swimmers (National - level swimmers of Malaysia) in anticipatory cue-utilization and corresponding autonomic phasic responses isolated from the tonic measures. Altogether two-hundred and twenty-five individuals having high athletic calibre, and holding top-positions in recently held National and International (Mostly ASEAN level) meets volunteered as the participants in this study. Simultaneous evaluation of autonomic arousal modulation (habituation paradigm tonic and phasic measures of skin conductance) was done when the swimmers were engaged in cue-related anticipatory task, associated with complex reaction performance. For this purpose, participants were evaluated intermittently (twice within the calendar year August 20 I 0 - July 20 II) with the identical research paradigm. Perceived sense of competence as well as the subjective feelings of apprehension of loosing was explored, and attempts were made to identify the obscure subjective expression of cognitive-emotional make-up, in explaining differential performance outcomes evident in the participants. Findings of multiple linear and polynomial regression analyses and predictive structural analyses however suggested direct, inverse and supportive relationships between measures of physiological arousal and psychological phenomena related to cognitive-affective and affective-motivational aspects of sports behaviour explaining pathways to both excellent and debilitative performance outcomes during practice sessions as well as in actual competitive situations.